2022
DOI: 10.3389/fneur.2022.1018521
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib and Etoricoxib may reduce risk of ischemic stroke in patients with rheumatoid arthritis: A nationwide retrospective cohort study

Abstract: Background and purposePrevious studies reported conflicting results about the risk of ischemic stroke associated with the use of non-steroidal anti-inflammatory drugs (NSAIDs) in patients with rheumatoid arthritis (RA). We aimed to investigate two specific COX-2 inhibitors, Celecoxib and Etoricoxib, and their corresponding effects on the risk of ischemic stroke in patients with RA.Patients and methods10,857 patients newly diagnosed with RA were identified and sampled from the Taiwanese National Health Insuranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Furthermore, a double-blind controlled study suggested that Nimodipine might offer therapeutic benefits in the management of acute stroke [ 75 ]. A population-based retrospective cohort study has shown that celecoxib reduce the risk of ischemic stroke in patients with rheumatoid arthritis in a dose- and time-dependent manner [ 76 ]. Relevant research also suggests that substances such as cyclosporine [ 77 ], vitamin E [ 78 ], deferoxamine [ 79 ], curcumin [ 80 ], and daidzein [ 81 ] may offer certain advantages in the prevention of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a double-blind controlled study suggested that Nimodipine might offer therapeutic benefits in the management of acute stroke [ 75 ]. A population-based retrospective cohort study has shown that celecoxib reduce the risk of ischemic stroke in patients with rheumatoid arthritis in a dose- and time-dependent manner [ 76 ]. Relevant research also suggests that substances such as cyclosporine [ 77 ], vitamin E [ 78 ], deferoxamine [ 79 ], curcumin [ 80 ], and daidzein [ 81 ] may offer certain advantages in the prevention of ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because of their specific effects on COX-2, which is not highly related to the time of drug exposure and the extent of relative selectivity. Among coxibs, celecoxib is associated with a relatively lower risk of cardiovascular events, which may be due to its low specificity for COX-2 ( 38 , 48 ). Johnsen et al ’s 2005 study ( 49 ) also supported this idea, but conflicted in another regard.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term use of Celecoxib may gradually lead to adverse effects such as increased blood pressure and a potentially prothrombotic environment, which can elevate the relative risk of ischemic stroke [ 152 ]. A population-based retrospective cohort study suggests that Celecoxib and Etoricoxib may be associated with a reduced risk of first-occurrence ischemic stroke in RA patients, with the risk reduction dependent on the dose and duration of use [ 153 ]. These paradoxical results of Celecoxib being protective at a higher dose in a shorter duration but harmful in a longer duration, as well as the neutral to slight protective effects of Etoricoxib, require further investigation to understand their underlying physiological mechanisms.…”
Section: The Association Between Nsaids and Risk Of Ischemic Stroke: ...mentioning
confidence: 99%